KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL OLIMPIADE TINGKAT SMP - Putri, Anggita Melati; Adirakasiwi, Alpha Galih (LPPM Universitas Bina Bangsa, 2024)
Mathematical representation abilities can be in the form of expressions, ideas or mathematical ideas, which originate from students' thoughts that emerge during learning in an effort to find mathematical solutions. There are three indicators of mathematical representation ability, namely verbal, pictorial and symbolic. The process of developing students' potential and thinking can be done by holding mathematics competitions or olympiads. The approach used in this research is qualitative with descriptive methods. Purposive sampling technique was used in this research to select samples with certain considerations. The aim of this research is to describe students' mathematical representation abilities in solving Olympiad questions. This research used a sample of 3 students each representing each high, medium and low representation ability group. Based on the results of research on visual representation abilities, some students already have high abilities, although there are some who are still medium or low. Meanwhile, in symbolic ability, there are many students whose abilities are high and only a few whose abilities are medium or low. For verbal representation, most students already have high abilities and only a few students have medium or low abilities